Stock assessment of Bombayduck Harpodon nehereus (Hamilton, 1822) from Gujarat coast using non-equilibrium production model - Mohammed Koya, K.; Sreenath, K. R.; Muktha, M.; Dash, Gyanranjan; Sen, Swathipriyanka; Zacharia, P. U.; Kumari, Sonia; Makwana, N. K.; Dhokia, H. K.; Polera, J. P.; Shiju, P. (Indian Journal of Fisheries, 2018)
Bombayduck Harpodon nehereus, harvested mainly by dol nets (stationary bag nets), has been a prolific fishery in the northern region of Arabian Sea and Bay of Bengal. Biomass and maximum sustainable yield (MSY) estimates for the Bombayduck stock in the Saurashtra region were obtained from a non-equilibrium surplus production model approach utilising catch per unit effort (CPUE) time series derived from fish landing data. Fox model was found to be the most appropriate defining model and the results demonstrated that the stock is currently being overexploited.